Gene‐Specific Variant Classifier (DPYD‐Varifier) to Identify Deleterious Alleles of Dihydropyrimidine Dehydrogenase. Issue 4 (2nd February 2018) - Shrestha, Shikshya; Zhang, Cheng; Jerde, Calvin R.; Nie, Qian; Li, Hu; Offer, Steven M.; Diasio, Robert B.
Abstract : Deleterious variants in dihydropyrimidine dehydrogenase (DPD, DPYD gene) can be highly predictive of clinical toxicity to the widely prescribed chemotherapeutic 5‐fluorouracil (5‐FU). However, there are very limited data pertaining to the functional consequences of the >450 reported no‐synonymous DPYD variants. We developed a DPYD ‐specific variant classifier (DPYD‐Varifier) using machine learning and in vitro functional data for 156 missense DPYD variants. The developed model showed 85% accuracy and outperformed other in silico prediction tools. An examination of feature importance within the model provided additional insight into functional aspects of the DPD protein relevant to 5‐FU toxicity. In the absence of clinical data for unstudied variants, prediction tools like DPYD‐Varifier have great potential to individualize medicine and improve the clinical decision‐making process.